2017
DOI: 10.1177/1179546817713204
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Hepatitis C Virus Treatment by Combination Therapy on Cardiovascular System

Abstract: BACKGROUNDThe prevalence of hepatitis C virus (HCV) in Egypt is quite high, and the combined oral direct-acting antiviral agents (DAAs) may have impressive results.OBJECTIVETo assess the cardiovascular effects of DAAs in patients with HCV.METHODSA total of 170 patients with HCV were divided into 2 groups: first group (100 patients) received triple combination therapy (pegylated interferon alfa, sofosbuvir, and ribavirin, whereas the second group (70 patients) received dual combination therapy (sofosbuvir and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 43 publications
6
10
1
Order By: Relevance
“…D’Agostino et al [ 18 ] found that HCV infection surges cardiovascular hazards, including heart failure. Reda et al [ 19 ] found that DAAs did not cause EF changes or new RWMAs in patients with normal baseline EF [ 14 ]. Our study found that DAAs in patients with midrange LVEF did not worsen their NYHA functional Class or EF by the end of treatment after three months.…”
Section: Discussionmentioning
confidence: 99%
“…D’Agostino et al [ 18 ] found that HCV infection surges cardiovascular hazards, including heart failure. Reda et al [ 19 ] found that DAAs did not cause EF changes or new RWMAs in patients with normal baseline EF [ 14 ]. Our study found that DAAs in patients with midrange LVEF did not worsen their NYHA functional Class or EF by the end of treatment after three months.…”
Section: Discussionmentioning
confidence: 99%
“…DAAs treatment utilized in a national Egyptian study for HCV infection treatment in patients with and without liver cirrhosis, did not cause any change in QTc interval. According to the study reported by Biomy et al, the cardiovascular impact of DAAs was assessed in 170 patients with HCV, and no arrhythmias were noted ( Biomy et al, 2017 ). A more recent study on DAAs in Egyptian patients also showed a benign on cardiovascular safety profile ( Ibrahim et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It included 170 patients with HCV infection: 100 patients received a triple combination therapy of pegylated IFN alfa, sofosbuvir, and ribavirin, while 70 patients received a dual combination therapy of sofosbuvir and simeprevir. No arrhythmias or changes in QTc interval were observed in any patients before and after therapy using the 12-lead surface ECG [16].…”
Section: Discussionmentioning
confidence: 84%